Is there any prognostic impact of intraductal carcinoma of prostate in initial diagnosed aggressively metastatic prostate cancer?. Issue 3 (13th October 2014) - Zhao, Tao; Liao, Banghua; Yao, Jin; Liu, Jiyan; Huang, Rui; Shen, Pengfei; Peng, Zhufeng; Gui, Haojun; Chen, Xueqin; Zhang, Peng; Zhu, Yuchun; Li, Xiang; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Intraductal carcinoma of prostate (IDC‐P) was usually found to be co‐exist with conventional aggressive prostate adenocarcinoma. The presence of IDC‐P was considered as an adverse pathological factor, which was associated with high Gleason score, large prostate volume and accelerated disease progression. However, no any information is available on the presence of IDC‐P diagnosed by needle biopsy in patients with metastatic prostate cancer. We investigated the incidence and prognostic value of intraductal carcinoma of prostate (IDC‐P) in initial diagnosed metastatic prostate cancer. METHODS We included 278 patients with initial diagnosed metastatic prostate cancer treated between 2008 and 2011, all the pathological diagnosis were from ultrasonic‐guided transperineal needle biopsy. IDC‐P was strictly defined according to Epstein's criteria. Analyzed factors included age, Eastern Cooperative Oncology Group (ECOG) score, clinical T staging, Gleason scores, baseline prostate specific antigen (PSA), alkaline phosphatase (ALP), hemoglobin (HGB), PSA normalization, and the presence of IDC‐P. RESULTS Totally, IDC‐P was found in 57/278 (20.5%) cases. Univariate analysis showed that, compared with cases without IDC‐P, cases with IDC‐P was definitely associated with much shorter CRPC‐free survival (CFS) time (46.05 ± 1.39 vs. 22.98 ± 1.80 months, P = 0.000) and OS time (50.38 ± 1.18 vs. 36.43 ± 2.10 months, P = 0.000). Multivariate analysis showed that the presence of IDC‐P was the only independent prognostic factor associated with poor CFS (HR = 4.886, P = 0.011) and OS (HR = 1.945, P = 0.020). Further sub‐analysis showed, even among patients with higher Gleason score (≥8) (n = 158), IDC‐P was still significantly and inversely associated with CFS and OS (the median CFS time: 40 versus 22 months; P = 0.000; the median OS time: 54 vs. 36 months, P = 0.000). Again, Cox's regression model confirmed that only the presence of IDC‐P was still not only an independent prognostic factor predicting shorter time of CRPC (HR = 4.031, P = 0.035), but also for poorer OS (HR = 2.499, P = 0.006). CONCLUSIONS The presence of IDC‐P in initial diagnosed metastatic prostate cancer, even among patients with more aggressive pattern, was firstly found to be significantly and independently associated with earlier occurrence of CRPC and poorer OS. We recommended the presence of IDC‐P should be a routine record in pathological report of clinical diagnosis and other potential therapeutic regimen might be added to intervene in the integrated therapy as early as possible. Prostate 75:225–232, 2015. © 2014 Wiley Periodicals, Inc.